Статус у сучасній літературній мові слів з ремаркою «діалектне» - Дзюбишина-Мельник, Наталія; Dzhiubyshyna-Melnyk, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2013)
Автор досліджує процеси проникнення слів з тереново обмежувальними ремарками у тлумачних словниках до орфографічних, кодифікаційне призначення яких надає цим словам літературно-нормативного статусу. Простежено динаміку у маркуванні актуалізованої лексики. Виявлено новоактуалізовану лексику – слова, що давніше не були залучені до нормативних словників. Проаналізовано зміни у змісті термінів-ремарок.The author explores the processes of words with territorially restrictive remarks in definition dictionaries penetrating into spelling dictionaries, the codification purpose of which gives these words literary norm status. The dynamics in marking actualized lexis was traced. The article reveals newly actualized lexis – words that have not been previously included into normative dictionaries. The changes in the contents of remark terms were analyzed. Based on comparison of the register and the remarks in a number of dictionaries the author notes that modern dictionary composers refocus on such enrichment sources of literary language as territorial dialects and achievements of western variant of literary language. The article characterizes tendencies of changes in defining the status of the words with territorially restrictive remarks in modern literary language. Certain observations as to including the lexis with such remarks into synonymic rows were made based on the principles of literary language.
The Status of Dialect Remarked Words in Modern Literary Language
Keywords: тереново обмежувальні ремарки; кодифікація лексики; статус слова в літературній мові; актуалізована та новоактуалізована лексика; territorially restrictive remarks; codification of lexis; the status of the word in literary language; actualized and newly actualized lexis